Comparison of the clinical performance of self-adhering flowable composite and resin-based pit and fissure sealant: a randomized clinical trial in pediatric patients - Elham Farokh Gisour; Fatemeh Jahanimoghadam; Reyhaneh Aftabi (BMC, 2024)
Abstract Background Self-adhering flowable composites are an innovative step in reducing the chair time of pit and fissure sealant treatment. This study aimed to compare the clinical performance of self-adhering flowable composite (SELF-ADH) and resin-based pit and fissure sealant (RBs). Methods This is a double-blinded, randomized, split-mouth clinical trial conducted on 80 fully erupted permanent mandibular first molars from 40 children aged 6 to 12 years. For each participant, two permanent molars were randomly treated with SELF-ADH or RB. All sealants were assessed at 3, 6, and 12-month follow-ups considering retention, marginal integrity, marginal discolouration, colour matching, surface texture, and caries recurrence. To analyse the data, logistic regression and Fisher's exact tests were used (significance level P < 0.05). Results At the 12-month follow-up, the number of fully retained sealants in the SELF-ADH group was significantly higher than that in the RB group (P < 0.001). Also, The success rate of marginal integrity in the SELF-ADH group was significantly greater than the the RB group (P = 0.031), while the rate of sealant marginal discolouration was higher in the RB group (P < 0.001). The incidence of recurrent caries in teeth with partial loss of sealant in both groups (P = 0.004, P < 0.001) increased significantly over time. Conclusion The retention and marginal integrity of the self-adhering flowable composite were significantly greater than those of the resin-based sealant. Therefore, due to the small number of work steps, flowable self-adhering composites can be used as alternatives to resin-based pit and fissure sealants. Trial registration This study was approved by the Ethics Committee of Kerman University of Medical Sciences with the code IR.KMU.REC.1399.556 and Iraninan Registry of Clinical Trials (IRCT) code IRCT20180521039763N4, as well as full compliance with the Declaration of Helsinki.